Epidemiological study of poisoning by pesticides in the state of Rondônia (Research, Society and Development, 2020)
The cases of poisoning by pesticides are a big problem to public health that affects innumerable people in Brazil, because the human exposition to these products can cause irreversible damages and even provoke death. The goal of this study is to describe the number of cases of poisoning by pesticides registered in the state of Rondônia located in the north region of Brasil. It was done an official data survey obtained with the system of the State Agency of Health Surveillance (AGEVISA). An analysis of the data relative to the period of 5 years, that comprehend the years from 2015 and 2019, took place. According to the obtained results, there was a total of 1.132 cases of poisoning by pesticides registered in the state of Rondônia during the period of this study. Evidencing that 58,57% of the cases registered correspond to male individuals and 41,43% to female, also the age range of the poisoned individuals varied from 1 to 90 years old, however the highest index of poisoning was obtained by the individuals that were from 22 to 50 years old. Besides that, it was observed that 89,29% of the cases of poisoning evolved to cure with no sequels and just 5,74% evolved to death. Thus concludes that the state of Rondônia has a significant margin of cases of poisoning by pesticides and that male individuals are more affected by poisoning and this can be related with their occupation.